Local Government Initiatives and Prospects for Mango Farming Community Capital Enhancement in Guimaras Province, Philippines - Noe John Joseph Endencio Sacramento (Journal of Local Government Issues (LOGOS), 2020)
Agricultural communities frequently encounter lack of support from various political actors. The local government units (LGUs) are responsible for initiating measures for improving community capitals towards fostering growth and development to mango farming communities. This descriptive qualitative study provides an understanding regarding the initiatives of the LGU in enhancing the community capitals in the Guimaras, Philippines mango farming community. The community capitals framework (CCF) served as a lens and guide. Semi-structured interview guides and participant observation are instrumental in data gathering from five key informants. Findings revealed that LGU provided various programs and initiatives to help enhancing the community capitals of the mango sector; thus, LGU as a political actor and development enabler has significant roles in fostering community development. Recommendations in this study are essential to the LGU further to enhance the community capitals of the mango farming sector. In gist, there is a crucial need to focus more on building social networks within the community, establish proper means for transporting the mango product, and strengthen community education on agriculture among the youth to be involved in the development of mango industry.